FORMATIVE ASSESSMENT IN HIGHER EDUCATION: USE OF ONLINE APPS AND LEARNING PLATFORM (Journal of Educational Sciences, 2020)
The paper contains research based on the course of English as a foreign language with 1st year students. It studies the formative assessment through written tasks, oral presentations and performance of students in the classroom as it is given in the curriculum of 1st semester. However, the curriculum for 2 semester involved major changes – switch to the formative assessment using digital technologies, including UIB EngApp, Kahoot and Moodle as an indispensable part of learning process. The aim of the paper was to study performance of the students in In 1st semester and in 2nd semester, find the differences in teaching process and define the efficiency of formative assessment with use of digital technologies. The researcher questions if formative assessment which applies digital technologies shows more positive influence to the result/ performance of a student. Digital technologies assessment involves online apps such as UIB EngApp, Kahoot, and learning platform Moodle. The researcher investigates how indirect feedback through digital technologies affects student’s performance; how delayed and instant feedback influences to overall refection of a student. The author held an experiment involving 1st year students students to collect data. Quantitative and qualitative methods were used to analyze the collected information to provide data on the results of formative assessment and performance of students. The findings provide results of students on final exams as well as results of formative assessment, which includes 4 major midterm tests and weekly tests on online apps and learning platforms. The study contains the results of 50 students, who during the experiment had formative assessment through digital technologies as well as traditional one. As we see formative assessment through online learning platforms and apps is very efficient for students performance. The ability to integrate digital technologies in and outside the classroom benefits students and learning process. Key words: formative assessment; higher education; digital education; online applications; learning platform.